2020
DOI: 10.1002/oa.2936
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative joint disease in the Chalcolithic population of El Mirador cave (Sierra de Atapuerca, Spain): The vertebral column

Abstract: Degenerative joint disease (DJD) is one of the most common pathological conditions identified in the archaeological record and remains a health problem in modern populations. This study aimed to evaluate DJD of the vertebral column in a sample from a Chalcolithic collective burial at El Mirador cave (Sierra de Atapuerca, Spain) dated to 4,880–4,390 years cal. BP. Most of the human remains recovered were commingled and are in a good state of preservation. Traditionally, far too little attention has been paid to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This is also the case for prehistoric Amerindians from Alabama where the greatest frequency of osteoarthritis occurred on T7-T10 and T12, with a peak at T9/T10 (Bridges, 1994). Other studies have identified the lower thoracic as particularly vulnerable to degenerative joint changes (Űstűndağ, 2009;Yustos et al, 2021); however, the upper thoracic is also cited as a location of extensive degenerative joint changes associated with osteoarthritis (Jurmain, 1990). Larsen (2015) suggests the lower thoracic vertebrae bear the greatest degree of mechanical loading.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This is also the case for prehistoric Amerindians from Alabama where the greatest frequency of osteoarthritis occurred on T7-T10 and T12, with a peak at T9/T10 (Bridges, 1994). Other studies have identified the lower thoracic as particularly vulnerable to degenerative joint changes (Űstűndağ, 2009;Yustos et al, 2021); however, the upper thoracic is also cited as a location of extensive degenerative joint changes associated with osteoarthritis (Jurmain, 1990). Larsen (2015) suggests the lower thoracic vertebrae bear the greatest degree of mechanical loading.…”
Section: Discussionmentioning
confidence: 80%
“…Walking erect places great strain on the thoracic vertebrae and has for millions of years (Cook et al, 1983) as well as more recently in prehistory (Trinkaus, 1985). Given this antiquity of vertebral degenerative markers it should be no surprise that deterioration of the spine is quite common in extant humans by 40 years (Bridges, 1994;Ortner, 2003;Quispe & Williams, 2019), but its expression is minor compared to individuals of more advanced ages (López-Barrales et al, 2015;Mays & Dungworth, 2009;Snodgrass, 2004;Űstűndağ, 2009;Yustos et al, 2021). Degeneration of the skeleton accelerates after 50 years and virtually everyone has some form of osteoarthritis by 65 years of age (Solomon, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-related changes of the vertebral column are generally advanced by daily work activities (i.e. heavy labor) or by chronic and habitual stress (Merbs 1996;Katzman et al 2010;Pili et al 2018;Aguirre et al 2020;Yustos et al 2021). Weposit that it is beneficial to study male-female differences in the age-related change patterns of the vertebral column in light of the male-female differences in biological and sociocultural elements.…”
Section: Introductionmentioning
confidence: 99%